Implementasi Konten Video Tiktok Sebagai Media Pembelajaran untuk Meningkatkan Pemahaman Bahasa Arab Siswa Kelas VII di MTs. Al-Ma’arif Badung: Implementation of Tiktok Video Content as a Learning Media to Improve Arabic Language Understanding for Class VII Students at MTs. Al-Ma’arif Badung - Prasetya, Penta Astari (Balai Diklat Keagamaan Denpasar, 2024)
Arabic is one of the mandatory subjects in the curriculum structure of Madrasah Tsanawiyah (MTs). However, in the learning process, students from elementary school graduates are less able to understand parts of the Arabic language that they have to receive at MTs, in contrast to students from Madrasah Ibtida'iyah graduates. These obstacles are of course challenges that must be overcome by MTs students who come from elementary school graduates. However, this should not be a reason to give up on learning Arabic. This research focuses on the aim of exploring the implementation of Tiktok video content as a learning medium to improve understanding of Arabic for class VII students at MTs. Al-Ma'arif Badung in overcoming problems that arise in the learning process. The method used is descriptive qualitative. The conclusion obtained in this research is that the implementation of Tiktok video content can be used as a useful learning medium for increasing students' understanding in learning Arabic in class VII MTs, for elementary school graduate students. This research provides recommendations to colleagues at MTs. Al-Ma'arif Badung to be more creative and innovative to develop interesting learning media in line with the development of generation Z.